2009
DOI: 10.1007/s00348-009-0613-x
|View full text |Cite
|
Sign up to set email alerts
|

On the vorticity characteristics of lobe-forced mixer at different configurations

Abstract: Lobe-forced mixer is one typical example of the passive flow controllers owing to its corrugated trailing edge. Besides the spanwise Kelvin-Helmholtz vortex shedding, streamwise vortices are also generated within its mixing layer. The geometrical configuration of the lobe significantly affects these two types of vortices, which in turn affects the mixing performance of the mixer. In the present investigation, characteristics of mixers with five different configurations were examined and evaluated for two veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
3
16
0
Order By: Relevance
“…Two discrete vortex cores appeared at the x/D,, = 0.36 plane (SVl and SV2). Similar to the experiments of Mao et al [15], an additional streamwise vortex pair (SV3 and SV4) was also formed at x/D/, = 0.72 plane due to the effect of the scalloped notch. The length scale of this additional streamwise vortex pair was much smaller than the lobe height.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Two discrete vortex cores appeared at the x/D,, = 0.36 plane (SVl and SV2). Similar to the experiments of Mao et al [15], an additional streamwise vortex pair (SV3 and SV4) was also formed at x/D/, = 0.72 plane due to the effect of the scalloped notch. The length scale of this additional streamwise vortex pair was much smaller than the lobe height.…”
Section: Resultssupporting
confidence: 83%
“…The core flow moved radially outward and the bypass flow moved radially inward. On the bypass side, the low shear region (between LM lines in yellow) was due to the low momentum fluid that accumulated in the lobe valley [15]. In addition, there was a triangle-shaped separation region (SP line in green) at the inlet plane of lobed mixer on the eore atid bypass sides due to the large penetration angle of this mixer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some researches were made for the advancement of lobed mixer contour, such as scalloping and scarfing of the lobes, lobe deflection, flow swirling, etc. Mao et al [23] compared scalloped and unscalloped planar mixers with the same penetration angle and trailing edge profiles. They showed that the streamwise vorticity was enhanced and its decay rate accelerated in scalloped mixers, largely because of the formation of two pairs of streamwise vortices at each lobe.…”
Section: Introductionmentioning
confidence: 99%
“…al. [8][9][10] found that there exist a large scale secondary flow downstream the flow field in a lobed mixer from numerical simulation and experiments. Paterson [11] confirmed this discovery by experiments and p roposed a preliminary explanation of the mechanism.…”
mentioning
confidence: 99%